Digitalization of the Process Landscape for Proprietary Bond Trading - Petrov, Timothy; Neussner, Wolfgang; Lackner, Maximilian (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
On the surface, the process landscape for fixed income securities trading within most banks has changed only slightly in the past four decades. The value chain remains divided amongst front-, middle-, and back office, with IT in support. Front office negotiates deals with customers and other banks, middle office manages risks and reporting, and back office ensures that payments are made in exchange for a transfer of the bonds that have been traded. Though these processes have gradually migrated to electronic mediums, much of the work in all functional areas remains manual. But the advent of digital technologies, primarily process automation software and data integration in an open software architecture, allows banks to dramatically change how the processes along the value chain are carried out. Repetitive and predictable tasks can be performed by automated software, allowing humans to concentrate on complex activities that require flexibility and discretion. Those tasks that remain in the hands of humans can also be made more efficient by extracting data from software applications along the entire process chain and providing them to the human user at the right point in time in the right system.